Determinación del coeficiente efectivo de convección para mezclas de gases producidos en la pirólisis de biosólidos (2019)
This article presents the methodology used to develop a computational tool for calculating the effective convection coefficient between the volatile and solid phase in a rotary kiln which pyrolysis of biosolids is carried out. The properties of the fluid are calculated as a mixture of components in the outlet of a rotary kiln. Knowing the mass fractions of the compounds present in the representative gas, a mathematical model is made to calculate the properties inside the kiln by raking into a count the height of the solid phase and the temperature of the volatile phase. Consequently, the effective coefficient of convection was calculated throughout the kiln.